Juridical Review of Cancellation of Notary Deed - Mohammad Roesli; Dyah Ayu Septi Arinningtyas; Adies Kadir (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2022)
The purpose of this study is to determine the factors causing the cancellation of a notary deed and to know the responsibilities of a notary on the cancellation of the deed. The research method uses descriptive methods to explain, describe, and describe in accordance with the problems that are closely related to this research, and comparative methods to find similarities and differences of opinion by experts to be used as a comparison. The results of the factors that cause the notary deed to be canceled, namely when the notary is proven to have committed a violation such as an unlawful act, for example in the making of a deed there is an element of coercion from the notary for one party to sign the deed, not reading the deed before the parties and other deed-making formal requirements are violated. by a notary. If it is proven, the notary must provide compensation to interested parties or who feel aggrieved for the deed made by the notary and the notary's responsibility for the canceled deed if one of the parties has defaulted and the notary has fulfilled the formal requirements for making the deed, the notary is not responsible or cannot be charged for the cancellation of the deed. But if the deed is canceled by the judiciary due to the negligence of the notary, then there are two sanctions that can be imposed on the notary, namely criminal sanctions and civil sanctions. Criminal sanctions are not regulated in the Notary Position Act, so that if there is a criminal violation such as the parties providing false information and the notary because of his negligence in pouring the false information into the deed, the notary can be subject to criminal sanctions contained in the Criminal Code. While civil sanctions that can be imposed on a notary is to compensate the parties who feel aggrieved by the deed he made. Compensation that can be borne by a notary in the form of material compensation or real and immaterial compensation or no compensation.